EXPANDING THE RANGE OF ORGANIC CAKES IN THE CONTEXT OF ECO-CONSUMERISM - TKACHENKO, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive analysis of methods applied to assess the negative influence of food products on both human health and the environment. The research highlights that modern approaches to food production and consumption cannot be limited to considerations of taste and nutritional value alone; rather, they must also incorporate parameters of safety, sustainability, and ecological compatibility. Within this framework, the study substantiates the feasibility and importance of utilizing organic raw materials for the development of innovative cupcake recipes as a healthier and more environmentally responsible alternative to conventional confectionery products.The analysis established that the key determinants of human health in relation to food products include food safety indicators, the presence or absence of carcinogenic effects, and the overall energy value of products. At the same time, the ecological footprint of food production is influenced by such critical parameters as acidification of ecosystems, emissions of greenhouse gases, extensive use of pesticides, and the consumption of water resources during agricultural production. By examining the primary ingredients typically used for cupcake preparation – flour, butter, sugar, and eggs – the study demonstrated that their organic analogues provide significant advantages. In particular, organic raw materials were shown to be associated with lower risks to human health, as well as reduced ecological pressure, especially regarding acidification levels, pesticide contamination, safety performance, and CO₂ emissions.To evaluate the sustainability dimension of newly developed products, the Sustainable Nutrition Index (SNI) was applied. Findings revealed that organic cupcakes obtained higher index values, ranging from 1.42 to 1.90, in contrast to the control samples, which displayed lower values between 0.9 and 1.1. The interpretation of these results confirmed that when the SNI exceeds the threshold of 1, the product can be categorized as belonging to the “green zone” of environmental impact, thus indicating its compliance with sustainability principles.Considering the growing role of eco-consumerism in modern society, where consumers increasingly strive to make informed choices aimed at minimizing their own ecological footprint, the expansion of the assortment of flour-based confectionery products manufactured from organic raw materials emerges as a significant and promising direction in commodity science. The research results therefore underline not only the scientific and practical relevance of developing organic confectionery recipes but also their potential contribution to broader strategies for promoting sustainable nutrition, advancing food safety, and fostering responsible consumer behavior.
Keywords: flour confectionery; cupcakes; organic food products; eco-consumerism; sustainable nutrition index